Redução do desperdício de hortifrúti no varejo por meio de marketing e tecnologias digitais - Souza, Michele de (Universidade do Vale do Rio dos Sinos, 2022)
This thesis analyzes how supermarkets and distributors can reduce food waste, specifically produce, by implementing marketing actions allied to digital technologies, Big Data Things, Machine Learning, Artificial Intelligence, and the Internet of technologies. Currently, little is known about the potential role of digital technologies in promoting the sustainability of supermarket chains in emerging economies. Thus, qualitative research was carried out on operating supermarkets and six distributors, which has not been carried out in qualitative research in Brazil. The results show that actions to reduce the number of food starters with an understanding of hortifrúti numbers. Through this understanding, a series of actions can be taken to reduce the effects of this opinion. This (between) the management of pricing, sales, operations, and operations can be underpinned by technologies such as augmented reality, including handling devices, storage, and display of items. Marketing initiatives simultaneously demonstrate how marketing departments can help a corporate society and supermarkets can help to be social.
Keywords: Desperdício de alimentos; Mitigação do desperdício de alimentos; Tecnologias digitais; Marketing; Varejo; Food waste; Mitigation of food waste; Digital technologies; Marketing; Retail; ACCNPQ::Engenharias::Engenharia de Produção